The Relationship Between Unsafe Action and Work Accidents in Production Workers in CV. SP Aluminum, Yogyakarta - Ummi Yatun Hasana; Widodo Hariyono (Universitas Ahmad Dahlan, 2025)
Background: Based on data from the Social Security Administration Agency (BPJS) Employment, it is stated that in 2019-2021 cases of work accidents continue to increase. According to Heinrich's domino theory, 88% of work accidents are caused by unsafe action, 10% are caused by unsafe conditions, and 2% are unavoidable (acts of God). CV. SP Aluminum is an aluminum craft industry in Yogyakarta engaged in casting, melting, and household appliances such as pans, pots, boilers, and others. From the results of interviews with workers, it was found that as many as 4 people had suffered scratches and 2 people had suffered injuries to their legs. Work accidents that occur are caused by unsafe action carried out by workers during the production process. The purpose of this study is to determine the relationship between unsafe action and work accidents in production workers in CV. SP Aluminum Yogyakarta City. Methods: This study used a Cross Sectional research design with Chi-Square analysis. The sample of this study amounted to 52 people obtained by total sampling technique. The instrument used was a questionnaire to find out the work accidents experienced and unsafe behaviors carried out by the respondents. Results: The results showed that there was a relationship between unsafe action (ρ= 0.001; PR=0.463) with work accidents in production workers at CV. SP Aluminum Yogyakarta City. Conclusion: There is a relationship between unsafe action and work accidents in production workers in CV. SP Aluminum Yogyakarta City.